A seven-year study about the epidemiology of smoking, alcohol, drugs and psychotropic consumption along with legal abortion in cases referred to forensic medicine centers in Fars since 2007-2013 - Fatemeh Ghodrati; Narges saadatmand; Mohammad Zarenezhad; Marzieh Akbarzadeh (International Journal of Medical Research and Review, 2016)
Introduction: Smoking, alcohol, and drugs consumption has increased among the women of child-bearing age. This rise and its negative consequences on the children's health have been considered by planners and WHO health centers. This study aimed to examine the prevalence of smoking, alcohol and drugs consumption among women of childbearing age who received abortion permission with either maternal or fetal causes from forensic medicine centers.Method: This is a descriptive-analytical study which was conducted during the years 2007- 2013. The total sample size was 1,664, of which 339 and 1325 had maternal and fetal abortion causes, respectively. The items registered in the questionnaire included demographic and obstetric variables, maternal or fetal causes of abortion, the simultaneous use of hookah and cigarettes, alcohol, psychotropic substances and drugs. The data were analyzed using descriptive statistics in SPSS software, version 11.5.Results: The most frequent age for women was between 25 and 30 years (31.5%). The legal abortion rate was 8.5% among women aged under 20 years old. The prevalence of substance consumption was 40.7% among women with either maternal or fetal cause abortion. It was estimated that 78.3% belonged to cigarette and hookah, 14.62% to drug and psychotropic and finally 5.31% to alcohol beverage consumption.Conclusion: In Iran, legal abortion approval is either by maternal or fetal causes. According to this study, the coincidence of pregnancy with cigarette and hookah consumption has the most prevalence. Substance abuse prevention, treatment, and control policy are one of the essential matters related to the care both before and during pregnancy.